Calcium interactions with Cx26 hemmichannel: Spatial association between MD simulations biding sites and variant pathogenicity. (December 2018) - Albano, Juan M.R.; Mussini, Nahuel; Toriano, Roxana; Facelli, Julio C.; Ferraro, Marta B.; Pickholz, Mónica
Graphical abstract: Highlights: Up to 4 microsecond atomistic molecular dynamics simulations of the CX26 hemichannel. Exploration of different calcium concentrations and initial conditions. Characterization of novel CX26 calcium binding sites. Spatially association of the 3D positions of the identified calcium binding sites with pathogenic variants in CJB2 gene. A first step on finding associations between molecular features and pathological variants of the Cx26 hemichannel. Abstract: Connexinophaties are a collective of diseases related to connexin channels and hemichannels. In particular many Cx26 alterations are strongly associated to human deafness. Calcium plays an important role on this structures regulation. Here, using calcium as a probe, extensive atomistic Molecular Dynamics simulations were performed on the Cx26 hemichannel embedded in a lipid bilayer. Exploring different initial conditions and calcium concentration, simulation reached ∼4 μs. Several analysis were carried out in order to reveal the calcium distribution and localization, such as electron density profiles, density maps and distance time evolution, which is directly associated to the interaction energy. Specific amino acid interactions with calcium and their stability were capture within this context. Few of these sites such as, GLU42, GLU47, GLY45 and ASP50, were already suggested in the literature. Besides, we identified novel calcium biding sites: ASP2, ASP117, ASP159, GLU114, GLU119, GLU120 and VAL226. To the best of our knowledge, this is the first time that these sites are reported within this context. Furthermore, since various pathologies involving the Cx26 hemichannel are associated with pathogenic variants in the corresponding CJB2 gene, using ClinVar, we were able to spatially associate the 3D positions of the identified calcium binding sites within the framework of this work with reported pathogenic variants in the CJB2 gene. This study presents a first step on finding associations between molecular features and pathological variants of the Cx26 hemichannel.